2018
DOI: 10.1080/21655979.2018.1470720
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas systems: ushering in the new genome editing era

Abstract: In recent years there has been great progress with the implementation and utilization of Clustered Regularly Interspaced Palindromic Repeats (CRISPR) and CRISPR-associated protein (Cas) systems in the world of genetic engineering. Many forms of CRISPR-Cas9 have been developed as genome editing tools and techniques and, most recently, several non-genome editing CRISPR-Cas systems have emerged. Most of the CRISPR-Cas systems have been classified as either Class I or Class II and are further divided among several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…1 Einnig hefur möguleiki á að geta haft áhrif á samsetningu erfðamengisins með líftaekni orðið að veruleika. 2 Samhliða hefur túlkun erfðaupplýsinga orðið sífellt flóknari. 1 Erfðaráðgjöf hefur verið hluti af heilbrigðisþjónustu allt frá miðri seinustu öld.…”
Section: Inngangurunclassified
See 1 more Smart Citation
“…1 Einnig hefur möguleiki á að geta haft áhrif á samsetningu erfðamengisins með líftaekni orðið að veruleika. 2 Samhliða hefur túlkun erfðaupplýsinga orðið sífellt flóknari. 1 Erfðaráðgjöf hefur verið hluti af heilbrigðisþjónustu allt frá miðri seinustu öld.…”
Section: Inngangurunclassified
“…Hákon Björn Högnason 1 Vigdís Fjóla Stefánsdóttir 1 Eirný Þöll Þórólfsdóttir 1 Jón Jóhannes Jónsson 1,2 Hans Tómas Björnsson 1,2,3 RESULTS: The number of individuals coming for genetic counselling increased every year over the time period. Reasons for referral were cancer-related in two-thirds of cases.…”
Section: E N G L I S H S U M M a R Ymentioning
confidence: 99%
“…Considering all the solutions available to breeders to improve pastures cultivars from a molecular perspective, in vitro culture and Agrobacterium transformation, in combination with other technologies such as genome-wide association studies [26] and CRISPR [27], play a central role in the association of genes with agronomic traits. In this regard, analysing genes associated with biotic and abiotic stresses can unleash the power of plant adaptation, creating better pastures adapted to a range of different environmental conditions.…”
Section: Cefotaxime Positive Effect On Shoot Regenerationmentioning
confidence: 99%
“…Together these studies suggest that an RNA‐mediated silencing pathway is normally involved to prevent DUX4 transcription, making this pathway an interesting potential therapeutic target. Himeda et al demonstrated the benefits of the use of CRISPR and dCas9 (catalytically dead Cas9) protein system (CRISPR‐dCas9) to reverse the epigenetic status of the FSHD locus . Targeting the transcriptional inhibitor KRAB to the DUX4 promoter through fusion with dCas9 repressed DUX4 and its downstream target genes in FSHD muscle cell cultures.…”
Section: Novel Potential Therapeutic Targetsmentioning
confidence: 99%